2003
DOI: 10.2176/nmc.43.589
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Seizures: Epidemiology, Pathology, and Prophylaxis

Abstract: The risk of epileptic seizures after craniotomy is extremely important but the incidence of postoperative epilepsy varies greatly, depending on the patient's conditions such as primary diseases, severity of surgical insult, and pre-existing epilepsy. Animal studies suggest that neurosurgical insults lead to seizures by two different mechanisms: One mechanism is mediated by free radical generation and the other by impaired ion balance across the cell membrane caused by ischemia or hypoxia. Conventional antiepil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
54
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 66 publications
0
54
0
2
Order By: Relevance
“…Pre-operative seizures attained 1/3 of study population and was comparable to frequency reported in other studies (2,12,16), while this study cohort had more early seizures than previous reports (11,12). Early seizures represent a well known risk factor for postsurgical epilepsy, as they correlate with the severity of the cerebral insult (14,20). In our study cohort incidence of late seizures (46% of study population) was quite elevated, occurring either in patients who had never experienced seizures before surgery and in subjects with pre-operative and early seizures.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Pre-operative seizures attained 1/3 of study population and was comparable to frequency reported in other studies (2,12,16), while this study cohort had more early seizures than previous reports (11,12). Early seizures represent a well known risk factor for postsurgical epilepsy, as they correlate with the severity of the cerebral insult (14,20). In our study cohort incidence of late seizures (46% of study population) was quite elevated, occurring either in patients who had never experienced seizures before surgery and in subjects with pre-operative and early seizures.…”
Section: Discussionmentioning
confidence: 70%
“…cerebral oedema, local inflammation, excitotoxic damage, oxidative stress, impairment of neuron metabolism) (5). Late postoperative seizures represent actual epilepsy and occur when acute symptomatic events are excluded (14). Onset of postoperative epilepsy has been widely investigated and several risk factors for late seizures have been described (e.g.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Surgical insult to the brain seems to generate free radicals, which in turn leads to formation of epileptogenic focus. However, some recent studies have not supported the prophylactic efficacy of AEDs in most craniotomized patients, but further studies are required 18) . We excluded patients with endovascular coil embolization, hence the contribution of surgical insult as a risk factor for late epilepsy could not be compared with that of minimally invasive endovascular technique.…”
Section: Other Risk Factorsmentioning
confidence: 99%